Pengaruh Variasi Pencil Lead Electrode (PLE) terhadap Deteksi Ion Logam Cu²⁺ menggunakan Modifikasi MnO₂ dengan Metode Voltametri Siklik - Mutiara Permatasari; Trisna Kumala Sari (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the use of modified pencil lead electrodes in electrochemical detection, despite their advantages as simple, low-cost, environmentally friendly, and highly sensitive heavy metal sensors. Copper ions (Cu²⁺) are essential elements for biological functions, but in excessive amounts, they become toxic and can damage vital organs such as the liver and kidneys. The aim of this research is to develop an effective electrochemical sensor for detecting Cu²⁺ ions by optimizing the type and modification of pencil lead electrodes. Electrode modification was performed using the drop-casting method with manganese dioxide (MnO₂) on three pencil hardness grades (2B, B, and HB), with voltammogram analysis based on the resulting current and redox potential. The results indicate that the MnO₂/PLE (2B) electrode demonstrated the most optimal performance compared to the other variations. This advantage is attributed to the electrocatalytic properties of MnO₂ and the higher graphite content in 2B pencils, which enhance the electrode’s conductivity and electrochemical response. These findings confirm that MnO₂/PLE (2B) is effective for Cu²⁺ ion detection and holds potential for development as an efficient electrochemical sensor for heavy metal analysis. Keywords: Cu²⁺ Ion; MnO₂; Pencil Electrode; Cyclic Voltammetry; Electrochemical Sensor